DNA barcodes for soil animal taxonomy - Rougerie, Rodolphe; Decaens, Thibaud; Deharveng, Louis; Porco, David; James, Sam W.; Chang, Chih-Han; Richard, Benoit; Potapov, Mikhail; Suhardjono, Yayuk; Hebert, Paul D. N (Pesquisa Agropecuaria Brasileira, 2010)
The biodiversity of soil communities remains very poorly known and understood. Soil biological sciences are strongly affected by the taxonomic crisis, and most groups of animals in that biota suffer from a strong taxonomic impediment. The objective of this work was to investigate how DNA barcoding – a novel method using a microgenomic tag for species identification and discrimination – permits better evaluation of the taxonomy of soil biota. A total of 1,152 barcode sequences were analyzed for two major groups of animals, collembolans and earthworms, which presented broad taxonomic and geographic sampling. Besides strongly reflecting the taxonomic impediment for both groups, with a large number of species-level divergent lineages remaining unnamed so far, the results also highlight a high level (15%) of cryptic diversity within known species of both earthworms and collembolans. These results are supportive of recent local studies using a similar approach. Within an impeded taxonomic system for soil animals, DNA-assisted identification tools can facilitate and improve biodiversity exploration and description. DNA-barcoding campaigns are rapidly developing in soil animals and the community of soil biologists is urged to embrace these methods.